Cyproheptadine as an appetite stimulant in children. Is it safe? - Philco Toaza, Priscila Elizabeth (2023)
Background: Cyproheptadine as an appetite stimulant in children. Is it safe? This drug has been used to increase appetite in pediatric patients, regardless of their sex or the presence of pathological conditions. The effectiveness of this drug in terms of weight gain and growth is still a matter of interest. due to the diversity of conclusions regarding its mechanism of action and therapeutic results. Methods: This bibliographic review of the scientific literature focused on research in order to obtain results around scientific articles related to the use of cyproheptadine as an appetite stimulant in pediatric patients. Results: all the articles analyzed concluded that cyproheptadine is an effective medication for weight gain in pediatric patients, based on appetite stimulation, totally independent of sex and the presence of pathological states. Conclusions: Cyproheptadine is a safe medication, and adequately tolerated in all pediatric patients. It is possible to measure the improvement in weight and growth indices in patients under twelve years of age, if consumption is for at least four consecutive weeks.